Principles of musculoskeletal injury prevention in wrestling. - Molnár, S. (International Journal of Wrestling Science, 2019)
Importance of the topicWrestling holds worldwide popularity,• Russia, former Soviet Union• Asia (Iran, Japan,Korea, Mongolia, India)• Europe (Scandinavia, Greece, Turkey, former East-block, France, Germany, Italy)• Traditional wrestling (Africa, Mongolia, Canary Island, Pakistan)• America: USA, Canada, Cuba, Brazil,United States: Large numbers of high school and college males (health system general DATAS!!!). But Barroso (Brasil), Kordi (Iran), Pasque, Otero (USA) and Yamaner (Turkey) is focusing on wrestlers!!!! However, the sport's arduous nature results in high injury rates.